Cast steel sheet, continuous casting method, and method for producing cast steel sheet
By controlling the solidification core density of the steel cast sheet surface and applying high viscosity protective slag and vibrating casting during continuous casting, the problem of surface cracks of the Ni-containing steel cast sheet is solved, which improves production efficiency and reduces manufacturing costs.
Patent Information
- Application Number
- CN202380062699.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-07-28
- Publication Date
- 2025-04-08
AI Technical Summary
Ni-containing steel castings are prone to cracks on the surface, resulting in long trimming treatment time, reduced productivity and increased manufacturing costs. Especially when the Ni content is less than 7.5%, the generation of surface cracks becomes a major problem in manufacturing.
By controlling the surface solidification core density of the steel cast sheet to be 0.35 units/mm2 or more, the size of the solidification unit is reduced, the segregation of S and P is reduced, and the stress acting on the interface of the solidification unit is dispersed, thereby suppressing the occurrence of surface cracks. Specific methods include adding high viscosity protective slag and vibrating casting during continuous casting to increase solidification core density.
It realizes the reduction of cracks on the surface of the steel casting sheet, shortens the trimming and processing time, improves productivity, and reduces manufacturing costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a steel slab containing Ni (nickel), a continuous casting method, and a method for producing the steel slab. Background Art
[0002] It is known that when Ni is added to steel, low temperature toughness is improved. Steel containing about 9% by mass of Ni (hereinafter also referred to as Ni-containing steel) is also called 9% Ni steel. 9% Ni steel is widely used as steel for low temperature welding structures such as LNG tanks because it can withstand use below -160°C.
[0003] However, it is known that Ni-containing steel is prone to have flaws on the surface. For example, in a cast piece after casting, many cracks (hereinafter also referred to as surface cracks) exist on the surface and near the surface.
[0004] It has been known that surface cracks of steel castings containing Ni occur along the grain boundaries of the coarse solidification structure. Specifically, it is believed that the surface cracks are caused by tensile stresses such as straightening stress, expansion stress, and thermal stress applied to the steel casting in the temperature range of 600 to 900°C, where the ductility of Ni-containing steel decreases, that is, in the secondary cooling zone of continuous casting.
[0005] More specifically, when tensile stress is applied to a steel cast, S (sulfur) and P (phosphorus) contained in the steel cast are concentrated in a specific region. The increase in the concentration of S (sulfur) and P (phosphorus) causes the grain boundaries of the steel cast to become embrittled. Therefore, the embrittled grain boundaries in this region are destroyed by the tensile stress, thereby generating surface cracks.
[0006] In order to prevent such surface cracks, the temperature of the steel slab is managed during the secondary cooling when the steel slab is cast. For example, Patent Document 1 discloses that when molten steel containing 5 to 10 mass % Ni is continuously cast, the cooling rate in the secondary cooling zone and the surface temperature of the slab are controlled.
[0007] Patent Document 2 discloses that when continuously casting a Ni-containing steel containing 8 to 10 mass % of Ni, the area reduction during casting is estimated and the secondary cooling intensity is controlled so that the area reduction becomes 50% or more.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 8-10919
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 8-33964 Summary of the invention
[0012] Problems to be solved by the invention
[0013] Thus, a continuous casting method for suppressing a large number of surface cracks has been proposed, but it is difficult to completely suppress the generation of surface cracks. When surface cracks are generated on a steel casting, the surface is removed by a so-called finishing process such as grinding the surface using a grinder or the like. Therefore, when the number of surface cracks increases, the scope of the finishing process and the processing time also become longer, resulting in a problem of reduced productivity and increased manufacturing costs.
[0014] However, in recent years, the price of Ni alloys has risen, and therefore the Ni content in steel has been reduced. For example, as a substitute for 9% Ni steel, alternative steels based on 7% Ni steel are being expanded. In addition, 5% Ni steel is used for ethylene liquefied fuel tanks. Thus, the demand for Ni-containing steels with a Ni content of less than 7.5 mass % is also very high.
[0015] In the case of a steel type having a relatively low Ni content of less than 7.5 mass %, the occurrence of surface cracks in the steel casting along the grain boundaries of the coarse solidified structure also becomes a problem in production.
[0016] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a steel slab containing 2.0 mass % or more and less than 7.5 mass % of Ni and having few surface cracks, a continuous casting method, and a method for producing the steel slab.
[0017] Methods used to solve problems
[0018] In order to solve the above-mentioned problems, the present invention has the following features. [1]
[0020] A steel cast piece containing Ni, which contains, by mass%, C: 0.03% to 0.10%, Si: 0.01% to 0.50%, Mn: 0.10% to 1.00%, P: 0.001% to 0.010%, S: 0.0001% to 0.0050%, Ni: 2.0% to less than 7.5%, Al: 0.010% to 0.080%, N: 0.0010% to 0.0050%, O: 0.0005% to 0.0040%, and the balance is Fe and unavoidable impurities, wherein the density of solidified nuclei on the surface of the steel cast piece is 0.35 pieces / mm 2 above. [2]
[0022] The steel slab according to [1], further comprising, in mass %, one or more selected from the group consisting of Cu: 0.03% to 1.50%, Cr: 0.03% to 1.00%, Mo: 0.02% to 1.00%, Nb: 0.003% to 0.100%, V: 0.003% to 0.100%, Ti: 0.005% to 0.020%, B: 0.0002% to 0.0025%, Ca: 0.0005% to 0.0050%, and Mg: 0.0005% to 0.0030%. [3]
[0024] A continuous casting method for casting the steel slab described in [1] or [2], comprising the step of adding a mold slag having a viscosity of 0.5 Pa·s (5 poise) or more at 1300°C into a casting mold. [4]
[0026] A continuous casting method for casting the steel slab described in [1] or [2], comprising the step of vibrating the casting mold at a vibration frequency of 80 cycles per minute or more. [5]
[0028] A continuous casting method, which is a continuous casting method for casting steel slabs described in [1] or [2], comprising: a step of adding protective slag having a viscosity of 0.5 Pa·s (5 poise) or more at 1300°C into a mold; and a step of vibrating the mold at a vibration frequency of more than 50 cycles per minute. [6]
[0030] A continuous casting method, which is a continuous casting method for casting the steel slab described in [1] or [2], comprising: a step of adding a protective slag having a viscosity of 0.15 Pa·s (1.5 poise) or more at 1300°C into a mold; and a step of vibrating the mold at a vibration frequency of more than 80 cycles per minute. [7]
[0032] A method for producing a steel ingot containing Ni, comprising: a trimming step of trimming a steel slab produced by the continuous casting method described in any one of [3] to [6]; and a heating step of heating the steel slab in a heating furnace at a heating temperature of 1100° C. or less after the trimming step.
[0033] Effects of the Invention
[0034] According to the present invention, the density of solidified nuclei on the surface of the steel casting is 0.35 / mm 2As described above, the size of the solidification unit can be made smaller than the existing size. As a result, the segregation of S (sulfur) and P (phosphorus) at the interface of the solidification unit can be reduced compared with the past. As a result, the embrittlement at the interface of the solidification unit can be suppressed. In addition, the stress acting on the interface of the solidification unit can be dispersed. As a result, the generation of cracks at the interface of the solidification unit can be suppressed, and the generation of cracks on the surface of the steel casting can be reduced. As a result, the processing time of the trimming process for removing cracks on the surface of the steel casting can be reduced, and the improvement of productivity and the reduction of manufacturing costs can be achieved. DETAILED DESCRIPTION
[0035] The Ni-containing steel slab (hereinafter also referred to as steel slab) of the present invention contains 2.0 mass % or more and less than 7.5 mass % of Ni. The steel slab can be used as low-temperature steel used in a temperature range below room temperature, for example.
[0036] The Ni-containing steel slab of the present invention contains, by mass%, C: 0.03% to 0.10%, Si: 0.01% to 0.50%, Mn: 0.10% to 1.00%, P: 0.001% to 0.010%, S: 0.0001% to 0.0050%, Ni: 2.0% to less than 7.5%, Al: 0.010% to 0.080%, N: 0.0010% to 0.0050%, O: 0.0005% to 0.0040%, and the balance is Fe and inevitable impurities.
[0037] The steel casting contains C (carbon) as a composition, which can ensure the strength of the base material. In particular, by making the content of C contained in the steel casting 0.03 mass% (hereinafter referred to as "%") or more, the strength of the base material can be good. When the content of C contained in the steel casting is excessive, cementite and island martensite, which are the starting points of brittle fracture, increase, and it is possible that appropriate toughness cannot be obtained. By making the content of C contained in the steel casting 0.10% or less, the toughness of the appropriate steel casting can be obtained.
[0038] The steel casting contains Si (silicon) as a composition, which can improve the deoxidation effect of removing oxygen contained in the steel casting. In addition, the steel casting contains Si as a composition, which can ensure the strength of the base material. When the amount of Si added increases, island martensite is generated in the structure of the heat-affected zone (HAZ), and there is a tendency that good toughness of the HAZ cannot be obtained.
[0039] That is, by setting the Si content of the steel casting to 0.50% or less, appropriate HAZ toughness can be ensured. By setting the Si content of the steel casting to 0.01% or more, an excellent deoxidation effect can be obtained, and the strength of the base material can be improved.
[0040] The steel casting can ensure the strength of the base material by including Mn as the composition. When the amount of Mn added increases, there is a tendency that good toughness of the HAZ cannot be obtained.
[0041] In particular, by setting the Mn content of the steel casting to 0.10% or more, the strength of the base material can be improved. In addition, by setting the Mn content of the steel casting to 1.00% or less, appropriate toughness of the HAZ can be ensured.
[0042] When the steel casting contains P (phosphorus) as a composition, there is a tendency to cause grain boundary embrittlement. Therefore, the steel casting may contain as low an amount of P (phosphorus) as possible as a composition. When the P (phosphorus) content of the steel casting is 0.010% or less, the promotion of surface cracks due to grain boundary embrittlement can be suppressed. Thus, the toughness of the base material and the HAZ can be improved.
[0043] In addition, when the P (phosphorus) content of the steel slab is 0.001% or more, an increase in the load of dephosphorization refining in the steelmaking process can be suppressed, and an increase in the manufacturing cost can be suppressed.
[0044] When the steel casting contains S (sulfur) as a composition, there is a tendency to cause grain boundary embrittlement. Therefore, the steel casting may contain as low an amount of S (sulfur) as possible as a composition. By having the S (sulfur) content of the steel casting be less than 0.0050%, the grain boundary embrittlement that promotes the generation of surface cracks can be suppressed. As a result, the toughness of the base material and the HAZ can be improved. In particular, S (sulfur) reduces the toughness of the steel casting in the form of inclusions such as MnS. Therefore, it is preferred that the S (sulfur) content of the steel casting is low.
[0045] Furthermore, by setting the S (sulfur) content of the steel slab to 0.0001% or more, it is possible to suppress an increase in the load of dephosphorization refining in the steelmaking process and to suppress an increase in the manufacturing cost.
[0046] As described above, the steel casting contains 2.0% or more and less than 7.5% Ni (nickel) as a composition. By containing the above-mentioned components, the steel casting can achieve the same physical properties as 9% Ni steel with a Ni content less than 9% Ni steel. From such a purpose, the Ni content of the steel casting can be 2.0% or more and less than 7.5%, preferably 6.5% or more and less than 7.5%. It should be noted that when the Ni content is less than 2.0%, there is a tendency that the toughness at low temperature brought by Ni cannot be obtained.
[0047] The steel casting contains Al (aluminum) as a composition, which can improve the deoxidation effect of removing oxygen contained in the steel casting. In addition, the steel casting contains Al (aluminum) as a composition, which can ensure the strength of the base material. When the addition amount of Al (aluminum) increases, there is a tendency for the base material and HAZ toughness to decrease due to coarse AlN.
[0048] That is, by setting the Al (aluminum) content of the steel casting to 0.080% or less, appropriate HAZ toughness can be ensured. In particular, by setting the Si content of the steel casting to 0.010% or more, an excellent deoxidation effect can be obtained.
[0049] When the steel casting contains N (nitrogen) as a composition, coarse metal nitrides such as AlN tend to be generated, and the toughness of the base material and HAZ tends to decrease. Therefore, the steel casting should contain as low an amount of N (nitrogen) as possible as a composition.
[0050] By setting the N (nitrogen) content of the steel casting to 0.0050% or less, it is possible to ensure appropriate toughness of the base material and HAZ. In addition, by setting the N (nitrogen) content of the steel casting to 0.0010% or more, it is possible to suppress the increase in the load of the denitrification treatment and the nitrogen absorption treatment in the steelmaking process, and to suppress the increase in the manufacturing cost.
[0051] When the steel casting contains O (oxygen) as a composition, there is a tendency to form inclusions and reduce the toughness of the base material and HAZ. Therefore, the steel casting may contain as little O (oxygen) as possible as a composition. When the O (oxygen) content of the steel casting is 0.0040% or less, the toughness of the base material and HAZ can be ensured appropriately.
[0052] In addition, by setting the O (oxygen) content of the steel slab to 0.0005% or more, it is possible to suppress an increase in the load of inclusion removal treatment in the steelmaking process and to suppress an increase in manufacturing cost.
[0053] In addition to containing the above-mentioned alloy elements, in order to improve the strength and toughness of the base material and the joint, the steel casting preferably also contains one or more selected from Cu, Cr, Mo, Nb, V, Ti, B, Ca, and Mg.
[0054] The steel casting may contain Cu (copper) as a composition. The steel casting can ensure the strength of the base material by containing Cu (copper) as a composition. When the amount of Cu (copper) added increases, there is a tendency that good toughness of the HAZ cannot be obtained.
[0055] That is, by making the Cu (copper) content of the steel casting slab 0.03% or more, good strength of the base material can be obtained. In addition, by making the Cu (copper) content of the steel casting slab 1.50% or less, appropriate toughness of the HAZ can be ensured.
[0056] The steel casting may contain Cr (chromium) as a composition. The steel casting can ensure the strength of the base material by containing Cr (chromium) as a composition. When the amount of Cr (chromium) added increases, there is a tendency that good toughness of the HAZ cannot be obtained.
[0057] That is, by setting the Cr (chromium) content of the steel casting to 0.03% or more, good strength of the base material can be obtained. In addition, by setting the Cr (chromium) content of the steel casting to 1.00% or less, appropriate toughness of the HAZ can be ensured.
[0058] The steel casting may contain Mo (molybdenum) as a composition. The steel casting can ensure the strength of the base material by containing Mo (molybdenum) as a composition. When the amount of Mo (molybdenum) added increases, there is a tendency that good toughness of the HAZ cannot be obtained.
[0059] That is, by making the Mo (molybdenum) content of the steel casting 0.02% or more, good strength of the base material can be obtained. In addition, by making the Mo (molybdenum) content of the steel casting 1.00% or less, appropriate toughness of the HAZ can be ensured.
[0060] The steel casting may contain Nb (niobium) as a composition. By containing Nb (niobium) as a composition, the steel casting can ensure the strength of the base material and achieve grain refinement of the crystal. When the amount of Nb (niobium) added increases, there is a tendency that good toughness of the HAZ cannot be obtained.
[0061] That is, by making the Nb (niobium) content of the steel casting 0.003% or more, it is possible to obtain good strength of the base material and achieve grain refinement of the crystals in the steel billet. In addition, by making the Nb (niobium) content of the steel casting 0.100% or less, it is possible to ensure appropriate toughness of the HAZ.
[0062] The steel casting may contain V (vanadium) as a composition. By containing V (vanadium) as a composition, the steel casting can ensure the strength of the base material and achieve grain refinement of the crystal. When the amount of V (vanadium) added increases, there is a tendency that good HAZ toughness cannot be obtained.
[0063] That is, by making the V (vanadium) content of the steel casting 0.003% or more, it is possible to obtain good strength of the base material and achieve grain refinement of the crystals in the steel billet. In addition, by making the V (vanadium) content of the steel casting 0.100% or less, it is possible to ensure appropriate toughness of the HAZ.
[0064] The steel casting may contain Ti (titanium) as a composition. By containing Ti (titanium) as a composition, the steel casting can ensure the strength of the base material and achieve grain refinement of the crystals in the steel billet. When the addition amount of Ti (titanium) increases, there is a tendency for the HAZ toughness to decrease due to coarse TiN.
[0065] That is, by making the Ti (titanium) content of the steel casting 0.005% or more, good strength of the base material can be obtained, and grain refinement of the crystal can be achieved. In addition, by making the Ti (titanium) content of the steel casting 0.020% or less, appropriate toughness of the HAZ can be ensured.
[0066] The steel casting may contain B (boron) as a composition. The steel casting may improve hardenability even in a very small amount by containing B (boron) as a composition. As a result, a significant increase in strength may be achieved when controlled cooling and quenching heat treatment are implemented. When the addition amount of B (boron) increases, there is a tendency for HAZ toughness to decrease by precipitating coarse boron nitrides and carborides.
[0067] That is, by setting the B (boron) content of the steel casting to 0.0002% or more, good strength can be obtained. In addition, by setting the B (boron) content of the steel casting to 0.0025% or less, appropriate toughness of the HAZ can be ensured.
[0068] The steel casting may contain Ca (calcium) as a composition. By containing Ca (calcium), the steel casting can control the morphology of inclusions and improve toughness. Ca (calcium) combines with S to form CaS. CaS can suppress ductility-reducing cracks at grain boundaries and achieve a reduction in surface cracks. When the amount of Ca (calcium) added increases, there is a tendency for the HAZ toughness to decrease due to the generation of coarse inclusions containing Ca.
[0069] That is, by setting the Ca (calcium) content of the steel casting to 0.0005% or more, good strength can be obtained. In addition, by setting the Ca (calcium) content of the steel casting to 0.0050% or less, appropriate toughness of the HAZ can be ensured.
[0070] The steel casting may contain Mg (magnesium) as a composition. By containing Mg (magnesium), the steel casting can control the morphology of inclusions and improve toughness. Mg (magnesium) combines with S to form MgS. MgS can suppress ductility-reducing cracks at grain boundaries.
[0071] In addition, MgS has a great effect of making austenite grain size fine, and can reduce surface cracks during continuous casting and rolling. When the amount of Mg (magnesium) added increases, coarse inclusions containing Mg are generated, which tends to reduce HAZ toughness.
[0072] That is, by setting the Mg (magnesium) content of the steel casting to 0.0005% or more, good strength can be obtained. In addition, by setting the Mg (magnesium) content of the steel casting to 0.0030% or less, appropriate toughness of the HAZ can be ensured.
[0073] The density of solidified nuclei on the surface of the steel casting is 0.35 / mm 2 The density of solidification nuclei on the surface is preferably 0.35 / mm 2 More than and less than 5.00 pieces / mm 2 , more preferably 0.50 pieces / mm 2 More than and less than 5.00 pieces / mm 2 .
[0074] The density of solidification nuclei is 5.00 / mm 2 When the temperature is above 5000 °C, it is necessary to use a stronger cooling powder, which makes the vibration frequency of the mold very high, so it is not preferred. That is, when the cooling of the mold becomes too strong, there is a tendency for the cooling of the steel casting in the mold to become uneven, causing the generation of longitudinal cracks to become significant. In addition, it is also easy to cause operational problems such as leakage caused by insufficient inflow of the powder. Therefore, it cannot be said that making the density of solidified nuclei extremely high (5.00 pieces / mm 2 The above) is valid.
[0075] The density of solidification nuclei on the surface of the steel casting can be measured by the following method. For example, on the surface of the steel casting, blocks (solidification units or dendrite units) with dendrite branches facing approximately the same direction are regarded as blocks grown from one solidification nucleus. That is, by calculating the number of such blocks per a predetermined area, the density of solidification nuclei can be calculated.
[0076] A detailed investigation of actual steel castings containing Ni revealed that the greater the number of solidification nuclei, the better the suppression of surface cracks. Specifically, if the density of solidification nuclei on the surface of the steel casting is 0.35 nuclei / mm 2 The above can effectively suppress surface cracks.
[0077] The continuous casting method for casting the steel slab described above will be described.
[0078] One of the methods for increasing the density of solidified nuclei on the surface of a continuously cast steel slab is to strengthen cooling during initial solidification of continuous casting, that is, to strengthen cooling within the mold.
[0079] Generally, continuous casting of steel slabs containing Ni includes a step of adding mold slag from the surface of molten steel in a mold. The mold slag functions as an antioxidant, a heat retaining agent, a lubricant for the mold and the solidified shell, and the like.
[0080] Since the mold flux flows into the gap between the solidified shell and the mold, the molten steel does not come into direct contact with the mold, and the molten steel is indirectly cooled by the mold via the inflow layer of the mold flux.
[0081] Therefore, by adjusting the viscosity of the mold flux, the thickness of the inflow layer can be formed thin, and by improving the heat dissipation capacity of the mold, the density of the solidification nuclei can be increased.
[0082] For example, the mold slag is composed of CaO, SiO2, Na2O, CaF2, Al2O3, etc. The thermal conductivity of the mold slag is significantly lower than the thermal conductivity of the molten steel as a metal and the copper constituting the continuous casting mold.
[0083] Heat dissipation from molten steel to the mold is affected by the thickness of the mold slag inflow layer. If the thickness of the mold slag inflow layer is thinner, the cooling efficiency of the mold becomes higher. If the thickness is thicker, the cooling efficiency decreases.
[0084] The thickness of the mold flux inflow layer can be estimated from the consumption of the mold flux. The thickness of the mold flux inflow layer is usually set to about 0.1 to 0.3 mm.
[0085] In order to make the mold flux flow layer thin, mold flux with high viscosity may be used. Therefore, for steel slabs, it is preferred to add mold flux with a viscosity of 0.5 Pa·s (5 poise) or more at 1300° C. to the casting mold for continuous casting.
[0086] The viscosity of the mold flux at 1300° C. is preferably 0.5 Pa·s (5 poise) or more and 5.0 Pa·s (50 poise) or less, and more preferably 1.0 Pa·s (10 poise) or more and 5.0 Pa·s (50 poise) or less.
[0087] By making the viscosity of the mold slag at 1300°C above 0.5 Pa·s (5 poise), the mold slag is less likely to flow into the gap between the solidified shell and the mold. Therefore, the thickness of the mold slag inflow layer can be made thinner, and the heat dissipation from the molten steel to the mold can be increased. As a result, the density of the solidified nuclei can be increased, that is, to 0.35 nuclei / mm 2 As described above, the occurrence of surface cracks can be suppressed.
[0088] The density of solidification nuclei can also be controlled by vibrating the mold at a predetermined vibration frequency (vibration, cycle). For example, due to the vibration of the mold, a portion of dendrites in the solidification process dissociates and adheres to the surface of the mold flux inflow layer. When the dendrites adhere to the surface of the mold flux inflow layer, solidification nuclei are generated from this portion. As a result, the density of solidification nuclei can be increased.
[0089] The continuous casting preferably includes, for example, a step of vibrating the mold at a frequency of 80 cycles or more per minute. The frequency of vibrating the mold is preferably 80 to 400 cycles, more preferably 100 to 400 cycles.
[0090] When the vibration frequency of the mold is less than 80 cycles, sufficient density of solidified nuclei may not be ensured. In addition, when the vibration frequency of the mold is greater than 400 cycles, there is a tendency for the mold to resonate and casting to become unstable.
[0091] The viscosity of the mold flux can be changed according to the vibration frequency (vibration, cycle) of the mold. For example, when the vibration frequency (vibration, cycle) of the mold is set to 50 cycles per minute, a mold flux with a viscosity of 0.5 Pa·s (5 poise) or more at 1300°C can be used. This can also make the density of solidified nuclei on the surface of the Ni-containing steel casting to be 0.35 / mm 2 above.
[0092] In addition, for example, when the vibration frequency (vibration, cycle) of the casting mold is set to 80 cycles per minute, a mold slag with a viscosity of 0.15 Pa·s (1.5 poise) or more at 1300°C can be used. This can also make the density of solidified nuclei on the surface of the Ni-containing steel casting to be 0.35 pieces / mm 2 above.
[0093] It is particularly preferred to set the vibration frequency (vibration, cycle) of the mold to 80 cycles per minute or more and use mold flux having a viscosity of 0.5 Pa·s (5 poise) or more at 1300° C. Under such conditions, surface cracks in the steel cast can be significantly reduced.
[0094] However, the surface of the steel casting containing Ni includes a surface including fine dimples and an extremely flat surface. The surface including dimples is considered to be formed by the destruction of grain boundaries in the ductility reduction temperature range of 600 to 900°C.
[0095] The flat surface is considered to be formed by a solidification crack based on its shape. More specifically, when the molten steel solidifies, the final solidification part is enriched with C, S, P, etc., and the melting point is lowered. The flat surface is formed by the contraction of the surrounding part where solidification has been completed while a low-melting-point liquid phase exists in the final solidification part.
[0096] More specifically, for surface cracks, when the solidified shell grows in the mold, solute elements such as C, S, and P are enriched at the boundary of two solidified units constituting the solidified shell. As a result, solidification cracks are generated due to the generation of a low-melting-point liquid phase. It is believed that with this solidification crack as the starting point, the crack further develops due to thermal stress in the secondary cooling zone, stress generated by bending straightening, etc.
[0097] Therefore, surface cracks cannot be sufficiently suppressed by merely relaxing the thermal stress and bending straightening stress in the secondary cooling zone which have been conventionally performed. In order to suppress surface cracks, it is important and necessary to suppress solidification cracks during the initial solidification in the mold.
[0098] The less the enrichment of solute elements in the final solidified portion, and the smaller the thermal stress acting on the final solidified portion, the less likely solidification cracks will occur. For example, when the size of the solidification unit becomes smaller, the cooling rate naturally becomes faster, and the enrichment of solute elements is suppressed. In addition, when the size of the solidification unit is small, the thermal stress is dispersed, and the thermal stress acting on the interface of each solidification unit becomes smaller. Reducing the size of the solidification unit is effective in preventing solidification cracks.
[0099] Generally, it is known that there is a correlation between the number of solidification units and the number of solidification nuclei, and the higher the density of solidification nuclei, the smaller the size of the solidification unit. Therefore, the size of the solidification unit can be reduced by increasing the density of solidification nuclei in the part where the molten steel contacts the mold.
[0100] That is, since the Ni-containing steel slab of the present invention has a high density of solidification nuclei, the size of the solidification unit can be reduced. As a result, a Ni-containing steel slab with few surface cracks can be provided.
[0101] According to the continuous casting method of the present invention, the initial solidification of the surface of the steel casting can be controlled. As a result, a plurality of solidification nuclei are generated, and the enrichment of impurity elements such as P (phosphorus) and S (sulfur) and C (carbon) to the interface of the solidification unit is reduced. Therefore, solidification cracks at the interface of the solidification unit can be suppressed. Therefore, the so-called surface cracks generated on the surface of the steel casting can be suppressed.
[0102] As described above, the density of solidified nuclei on the surface of the steel slab containing Ni according to the present invention is 0.35 pieces / mm 2 As a result, the size of the solidification unit can be reduced. As a result, since the enrichment of S and P at the interface of the solidification unit is reduced, the embrittlement at the interface of the solidification unit can be suppressed. In addition, the stress acting on the interface of the solidification unit is also dispersed, and the solidification cracks at the interface of the solidification unit can be suppressed. As a result, the generation of cracks on the surface of the steel casting can be reduced.
[0103] In addition, in the present invention, a method for manufacturing a steel slab using a steel slab produced by the above-mentioned continuous casting is described. The method for manufacturing a steel slab containing Ni includes: a trimming step of trimming the steel slab produced by the continuous casting method; and a heating step of heating the steel slab in a heating furnace at a heating temperature of 1100° C. or less after the trimming step.
[0104] In the method for manufacturing a steel sheet, a steel sheet is manufactured using a steel billet produced by continuous casting of molten steel. Conventionally, the produced steel billet is heated at 1000 to 1200°C (first heating treatment). The steel billet subjected to the first heating is pre-rolled to a thickness of about 60 to 90% (light initial rolling). Grinding and finishing treatments to remove defects are performed until the defects on the pre-rolled steel billet disappear. The steel billet subjected to the finishing treatment is heated at 1000 to 1200°C (second heating treatment). The steel billet subjected to the second heating treatment is rolled (main rolling).
[0105] In the steel casting produced by the existing production method, cracks accompanied by oxide scale were confirmed at the austenite grain boundary. The composition of the oxide scale contains Fe2SiO4 (fayalite). As one of the causes of cracks accompanied by oxide scale, the presence of Fe2SiO4 (fayalite) is listed.
[0106] Fe2SiO4 scale is generated in steel containing more than 0.05% silicon (Si) along with the generation of Fe2SiO4. It should be noted that the eutectic temperature of Fe2SiO4 and wüstite (FeO) is 1170°C. Fe2SiO4 is a liquid oxide above the eutectic temperature.
[0107] When Fe2SiO4 scale is generated, the grain boundary becomes fragile. Since Fe2SiO4 scale is in liquid phase at high temperature, it is easy to diffuse into the grain boundary and deep part of the parent phase.
[0108] After the Fe2SiO4 scale is generated, grain boundary cracks are generated due to thermal stress and strain during rolling. Therefore, even if the generation of surface flaws is suppressed during continuous casting, flaws are formed on the surface of the steel casting as a product due to the presence of Fe2SiO4 (fayalite).
[0109] Therefore, when manufacturing steel slabs, it is preferred to perform the manufacturing process under conditions below the eutectic temperature of Fe2SiO4. In other words, it is preferred to set the heating temperature of the heating furnace below the eutectic temperature of Fe2SiO4.
[0110] It should be noted that the formation of Fe2SiO4 scale in the grain boundary is also related to the segregation of elements such as P and S in this region. Therefore, for example, even if the manufacturing process is carried out at a temperature below the eutectic temperature of about 1100°C, there is a case where liquid phase Fe2SiO4 scale is generated in part of this region.
[0111] Therefore, in order to suppress the occurrence of cracks associated with Fe2SiO4 scale, the heating process is preferably performed at a temperature below 1100° C., and more preferably at a temperature below 1050° C. In addition, it is preferred to perform the rolling process after heating the steel billet in the heating process under such conditions.
[0112] However, when a steel slab is produced by controlling the density of solidification nuclei by the continuous casting method of the present invention, since the steel slab has better toughness than conventional steel slabs, a steel cast piece can be produced without performing preliminary rolling such as light blooming.
[0113] Therefore, when a steel billet is produced by controlling the density of solidification nuclei by the continuous casting method of the present invention, a steel cast piece can be produced by performing the following (1) to (3).
[0114] (1) A finishing process is performed to remove defects by grinding about 3 to 6 mm from the surface until the defects of the generated steel billet disappear (finishing process).
[0115] (2) The steel billet that has been subjected to the trimming treatment is heated at 1100° C. or lower (heating step).
[0116] (3) The steel billet that has been subjected to the heating step is rolled (main rolling).
[0117] Thus, by performing heat treatment on the steel billet at a temperature of 1100°C or less, the surface defects of the steel casting (product) can be suppressed to a level that does not cause problems as a product. In other words, by manufacturing the steel casting in this way, the generation of Fe2SiO4 oxide scale can be suppressed, and the steel casting (product) in which the generation of defects in the primary rolling process is suppressed can be manufactured.
[0118] Example 1
[0119] Molten steel was produced by melting 3.5%Ni steel having a Ni content of 3.5 mass %, 5%Ni steel having a Ni content of 5.0 mass %, and 5%Ni steel having a Ni content of 7.0 mass %. A converter and an RH vacuum degassing device were used to produce the molten steel.
[0120] The experiment of casting the molten steel was carried out using a vertical curved billet continuous casting machine. The thickness of the vertical curved billet continuous casting machine was 250 mm and the width was 2100 mm. The experiment was carried out for a total of 20 heatings (Test No. 1 to 20). The chemical composition of Test No. 1 to 20 is shown in Table 1. The casting conditions of Test No. 1 to 20 in the continuous casting machine are shown in Table 2.
[0121]
[0122]
[0123] For Test No. 1, 4, 6, 9, 11, 14, and 16, the casting speed was 0.8 m / min. The amplitude of the vibration of the mold was 8 mm. The vibration frequency of the vibration was 60 cycles per minute. For the mold flux, a mold flux with a viscosity of 0.20 Pa·s at 1300° C. was used.
[0124] For Test Nos. 2, 3, 5, 7, 8, 10, 12, 13, 15, 17, and 18, the casting speed was 0.8 m / min. The amplitude of the vibration of the mold was 8 mm. The vibration frequency of the vibration was 60 cycles per minute. For the mold slag, a mold slag with a viscosity of 0.06 to 2.00 Pa·s at 1300°C was used.
[0125] For Test No. 19, the casting speed was 0.8 m / min. The amplitude of the vibration of the mold was 8 mm. The vibration frequency of the vibration was 80 cycles per minute. For the mold flux, a mold flux with a viscosity of 0.20 Pa·s at 1300° C. was used.
[0126] For Test No. 20, the casting speed was 0.8 m / min. The amplitude of the vibration of the mold was 8 mm. The vibration frequency of the vibration was 80 cycles per minute. For the mold flux, a mold flux with a viscosity of 0.5 Pa·s at 1300° C. was used.
[0127] The steel slabs after casting were cut into 300 mm lengths. The cut samples were subjected to the following treatments and then evaluated for surface cracks. The surface of each sample was shot peened to remove the oxide film on the surface. Then, the surface cracks were identified by penetrant testing. For the identified surface cracks, the length and number of the cracks were measured.
[0128] In order to investigate the depth of surface cracks, grinding was performed to positions 3 mm, 6 mm, and 9 mm from the surface. For each surface after grinding, surface cracks were identified by penetrant testing. For the identified surface cracks, the length and number of cracks were measured.
[0129] The density of solidified nuclei on the surface of the cast piece is measured by the following method. A sample is cut from the surface of the steel cast piece, and the oxide film on the surface is removed by shot blasting. The surface of the steel cast piece from which the oxide film has been removed is mirror-polished and etched with picric acid to reveal the solidified structure.
[0130] A photograph of the solidified structure is taken. In the photograph, blocks (solidification units or dendrite units) with dendrite branches oriented in approximately the same direction are regarded as blocks grown from one solidification nucleus. The density of solidification nuclei is calculated by counting the number of such blocks per predetermined area.
[0131] Specifically, the blocks captured in the photo of the solidified structure are counted as the number of solidification units, and the number is divided by the area occupied by the solidification unit to obtain the density of the solidification nucleus. In addition, the size of the solidification unit tends to be small near the vibration mark and to increase as it moves away from the vibration mark. Therefore, the range for counting the solidification units is from one vibration mark to the other vibration marks adjacent to each other, and the average value is obtained.
[0132] Table 3 shows the results of investigating the density of solidification nuclei and the total crack length (crack length×number of cracks) of Test Nos. 1 to 20.
[0133]
[0134] In Test No. 1, 6, 11, and 16, the density of solidification nuclei was less than 0.35 / mm 2 A large number of surface cracks occurred in Test Nos. 1, 5, 9, and 13. In addition, in Test Nos. 1, 6, 11, and 16, cracks occurred at a position 3 mm or 6 mm away from the surface.
[0135] On the other hand, in Test Nos. 2 to 5, 7 to 10, 12 to 15, and 17 to 20, the density ratio of solidification nuclei was 0.35 / mm. 2 Referring to the results of Test Nos. 2 to 5, 7 to 10, 12 to 15, and 17 to 20, as the density of solidification nuclei increases, the occurrence of surface cracks decreases.
[0136] In particular, when the density of solidification nuclei is greater than 1.50 / mm 2 A significant reduction in surface cracks was observed in Test Nos. 5, 10, 15, and 20. In the remarks column of Table 3, tests within the scope of the present invention are indicated as "invention examples", and the others are indicated as "comparative examples".
[0137] (Manufacturing test of steel castings)
[0138] The steel slabs of Test Nos. 1 to 20 were subjected to heating and rolling steps by the following method to produce steel slabs (hereinafter also referred to as products). The products were produced by "Method A" corresponding to the conventional production method and "Method B" corresponding to the production method of the present invention.
[0139] (Method A)
[0140] A finishing treatment is performed to remove defects by grinding about 3 to 6 mm from the surface until the defects on the generated billet disappear. The billet that has been subjected to the finishing treatment is heated at 1050°C or 1200°C (first heating treatment). The billet that has been subjected to the first heating is pre-rolled (light initial rolling) to reduce the thickness from 250 mm to 190 mm. A finishing treatment is performed to remove defects by grinding about 3 to 6 mm from the surface until the defects on the pre-rolled billet disappear. The billet that has been subjected to the finishing treatment is heated at 1050°C or 1200°C (second heating treatment). The billet that has been subjected to the second heating treatment is subjected to main rolling to reduce the thickness from 190 mm to 25 mm. Then, defects on the surfaces at a distance of 3 mm, 6 mm, and 9 mm from the surface are inspected (hereinafter also referred to as product inspection).
[0141] (Method B)
[0142] A finishing process (finishing process) is performed to remove defects by grinding about 3 to 6 mm from the surface until the defects on the generated steel billet disappear. The steel billet that has undergone the finishing process is heated at 1050°C or 1200°C (heating process). The steel billet that has undergone the heating process is mainly rolled to reduce the thickness from 250 mm to 25 mm. Then, the product inspection is performed on the surface at a distance of 3 mm, 6 mm, and 9 mm from the surface.
[0143] Product inspection is evaluated according to the following three levels.
[0144] ○: The product has no defects
[0145] △: Minor product defects (can be used as a finished product after repair)
[0146] ×: A large number of product defects (defects remain even after finishing and cannot be used as a product)
[0147] Table 4 shows the occurrence of surface defects in each product after rolling.
[0148]
[0149] When the steel billet was produced by method A at a heating temperature of 1200° C., a small amount of defects of the product remained, but the defects were within a range that did not hinder production.
[0150] For the test No. 1, 6, and 11 of 5-7% Ni steel, the amount of trimming treatment was 9 mm. In contrast, the amount of trimming treatment for the other 5-7% Ni steel tests was 3-6 mm. In addition, for the test No. 16 of 3.5% Ni steel, the amount of trimming treatment was 6 mm. In contrast, the amount of trimming treatment for the other tests of 3.5% Ni steel was 3 mm. That is, compared with the comparative example, the example of the present invention can significantly reduce the amount of trimming treatment.
[0151] For the steel billets of Test Nos. 2 to 5, 7 to 10, 12 to 15, and 17 to 20, the heating temperature was 1050°C, and even without light initial rolling, the evaluation of "○: no product defect" was obtained. Therefore, for these tests, the process cost can be greatly reduced and the quality of the product can be stably improved.
[0152] The defects (defective parts) of the products were investigated using EPMA (Electron Probe MicroAnalyzer). The results showed that in the test example of heating the steel billet at 1200°C, a large amount of Fe2SiO4 oxide scale was contained in the defects. It is known that the influence of oxide scale when heating the steel billet has a great influence on the formation of defects.
Claims
1. A steel cast containing Ni, which contains, by mass%, C: 0.03% to 0.10%, Si: 0.01% to 0.50%, Mn: 0.10% to 1.00%, P: 0.001% to 0.010%, S: 0.0001% to 0.0050%, Ni: 2.0% to less than 7.5%, Al: 0.010% to 0.080%, N: 0.0010% to 0.0050%, O: 0.0005% to 0.0040%, and the balance is Fe and unavoidable impurities, wherein the density of solidified nuclei on the surface of the steel cast is 0.35 pieces / mm 2 above.
2. The steel casting according to claim 1, wherein: It also contains, in mass %, one or more selected from the group consisting of Cu: 0.03% to 1.50%, Cr: 0.03% to 1.00%, Mo: 0.02% to 1.00%, Nb: 0.003% to 0.100%, V: 0.003% to 0.100%, Ti: 0.005% to 0.020%, B: 0.0002% to 0.0025%, Ca: 0.0005% to 0.0050%, and Mg: 0.0005% to 0.0030%.
3. A continuous casting method, which is a continuous casting method for casting the steel slab according to claim 1 or 2, wherein: The method comprises the step of adding a mold slag having a viscosity of 0.5 Pa·s (5 poise) or more at 1300° C. into a mold.
4. A continuous casting method, which is a continuous casting method for casting the steel slab according to claim 1 or 2, wherein: The method comprises vibrating the mold at a frequency of more than 80 cycles per minute.
5. A continuous casting method, which is a continuous casting method for casting the steel slab according to claim 1 or 2, wherein: include: A step of adding a mold slag having a viscosity of 0.5 Pa·s (5 poise) or more at 1300° C. into a casting mold; as well as A process of vibrating the mold at a frequency of 50 cycles per minute or more.
6. A continuous casting method, which is a continuous casting method for casting the steel slab according to claim 1 or 2, wherein: include: A step of adding a mold slag having a viscosity of 0.15 Pa·s (1.5 poise) or more at 1300° C. into a mold; as well as A process of vibrating the mold at a frequency of 80 cycles per minute or more.
7. A method for producing a steel casting containing Ni, comprising: A finishing step of performing a finishing treatment on the steel billet produced by the continuous casting method according to claim 3; as well as A heating step of heating the steel slab in a heating furnace at a heating temperature of 1100° C. or less after the trimming step.
8. A method for producing a steel casting containing Ni, comprising: A finishing step of performing a finishing treatment on the steel billet produced by the continuous casting method according to claim 4; as well as A heating step of heating the steel slab in a heating furnace at a heating temperature of 1100° C. or less after the trimming step.
9. A method for producing a steel casting containing Ni, comprising: A finishing step of performing a finishing treatment on the steel billet produced by the continuous casting method according to claim 5; as well as A heating step of heating the steel slab in a heating furnace at a heating temperature of 1100° C. or less after the trimming step.
10. A method for producing a steel casting containing Ni, comprising: A finishing step of performing a finishing treatment on the steel billet produced by the continuous casting method according to claim 6; as well as A heating step of heating the steel slab in a heating furnace at a heating temperature of 1100° C. or less after the trimming step.
Citation Information
Patent Citations
Method for continuously casting nickel-containing steel
JP1996010919A
Continuous casting method of high ni steel
JP1996033964A